DNA DAMAGE RESPONSE IN CANCER: GUARDIAN AND TARGET - Mrs. M.Menaka (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
The DNA Damage Response (DDR) is a multifaceted network of cellular pathways responsible for identifying, signaling, and repairing various forms of DNA lesions. Its role in maintaining genomic integrity is essential for cellular homeostasis and the prevention of malignancy. However, cancers often exhibit DDR deficiencies, enabling genomic instability while also creating therapeutic vulnerabilities. This review outlines the central mechanisms of the DDR, its dysregulation in cancer, and the emerging strategies to therapeutically exploit DDR deficiencies in oncology.